An Evaluation of the Teachers’ Perception on Professional Development in Maltese State Schools at Primary Level - Fenech, Maria Sabrina (2018)
In recent years, the education system in Malta has been changing to provide students a better education. Offering quality education requires teachers who are not only qualified and warranted but able to keep themselves in-line with the on-going changes of tomorrow’s society. Professional development is the key for teachers to up-skill and re-skill their competencies as to be able to guide others. The main aim of this study was to evaluate the perception of primary state school teachers in Malta about professional development by finding ways of how such a system can be improved locally to become more effective. To be able to reach the aim, it was best to make teachers central to the study as to evaluate their perspectives about their own development. A pragmatic worldview philosophical approach was chosen in order to address the research issue. The study was conducted within two primary schools where questionnaires were distributed to primary teachers. As to validate the findings, semi-structured interviews were conducted with two primary teachers from each school followed by another two interviews with the respective head of school. The mixed methodology helped in confirming the data collected from different perspectives. The findings showed that local teachers know about the importance of professional development and are willing to participate in various courses which eventually help the teachers in widening their capacity or enhance teaching and learning. However, due to a number of factors, teachers locally participate mostly in compulsory professional development activities only even though various other courses are available. Teachers have described that the professional development offered is not always effective and made their suggestions in order to bring a positive change.